Comparison of P-POSSUM and E-POSSUM in defining prognosis in acute abdomen cases - Nambi, Deepa; Giridharan, Bhanumati (International Surgery Journal, 2019)
Background: The study attempts to define prognosis in acute abdomen cases using elderly modification (E-POSSUM) and compares its performance with physiological and operative severity score for the enumeration of mortality and morbidity (POSSUM) and Portsmouth modification- (P-POSSUM). Methods: A non-randomized, prospective study was conducted between January 2016-November 2018 in 260 patients, aged ≥60 years old, undergoing elective and emergency general surgeries. Baseline characteristics, PS at the time of admission, surgery and OS at the moment of the patient’s discharge was obtained after formal ethical consent. The follow up period was 30 days post-surgery, and complications if any, were noted. Results: When exponential analysis was applied, POSSUM over predicted morbidity in low risk group (<30%), and though, it accurately predicted morbidity in higher risk strata, it was not statistically significant. Similarly, E-POSSUM accurately predicted morbidity for risk strata 60 -100 however, it was not significant when chi-square test was applied. However, when compared to POSSUM morbidity equation, E-POSSUM showed signiﬁcant difference for risk strata 40-100 and 50-100. When exponential analysis was applied, E-POSSUM accurately predicted post-operative mortality similar to P-POSSUM. However, based on observed and expected ratio, E-POSSUM outperforms P-POSSUM in prediction of mortality. Conclusions: Exponential analysis of E-POSSUM better predicts morbidity and post-operative mortality risk in various acute abdomen cases when compared to POSSUM morbidity and P-POSSUM mortality equation. Hence, E-POSSUM is a valid scoring system for predicting morbidity and mortality risk in elderly patients undergoing elective and emergency surgery for acute abdomen.